Truth and consequences : life inside the Madoff family - Sandell, Laurie (Little, Brown, 2011)
With unprecedented access to the surviving family members-wife Ruth, son Andrew and his fiancé Catherine Hooper-journalist Laurie Sandell reveals the personal details behind the headlines. How did Andrew and Mark, the sons who'd spent their lives believing in and building their own families around their father's business first learn of the massive deception? How does a wife, who adored her husband since they were teenagers, begin to understand the ramifications of his actions? The Madoffs were a tight-knit-even claustrophobic-clan, sticking together through marriages, divorces, and illnesses. But the pressures of enduring the massive scandal push them to their breaking points, most of all son Mark, whose suicide is one of the many tragedies that grew in the wake of the scandal.